Maritime piracy: the unseen threat to shipping - Seow, Gina Tian Ru (Nanyang Technological University, 2023)
Piracy, a persistent maritime issue, poses significant threats to vessel safety and the mental well-being of seafarers. This report explores pirates’ choice of attack on various vessels, while shedding light on the mental well-being of seafarers during their voyages.